The Effect of Transitional Care on 30-Day Outcomes in Patients Hospitalised With Acute Heart Failure - Driscoll, A.; Dinh, D.; Prior, D.; Kaye, D.; Hare, D.; Neil, C.; Lockwood, S.; Brennan, A.; Lefkovits, J.; Carruthers, H.; Amerena, J.; Cooke, J.C.; et al. (ELSEVIER SCIENCE INC, 2020)
Background: Patients admitted to hospital with acute heart failure (AHF) are at increased risk of readmission and mortality post-discharge. The aim of the study was to examine health service utilisation within 30 days post-discharge from an AHF hospitalisation. Methods: This was a prospective, observational, non-randomised study of consecutive patients hospitalised with acute HF to one of 16 Victorian hospitals over a 30-day period each year and followed up for 30 days post-discharge. The project was conducted annually over three consecutive years from 2015 to 2017. Results: Of the 1,197 patients, 56.3% were male with an average age of 77±13.23 years. Over half of the patients (711, 62.5%) were referred to an outpatient clinic and a third (391, 34.4%) to a HF disease management program. In-hospital mortality was 5.1% with 30 day-mortality of 9% and readmission rate of 24.4%. Patients who experienced a subsequent readmission less than 10 days post-discharge and between 11 and 20 days post-discharge had a five- to six-fold increase in risk of mortality (adjusted OR 5.02, 95% CI 2.11–11.97; OR 6.45, 95% CI 2.69–15.42; respectively) compared to patients who were not readmitted to hospital. An outpatient appointment within 30 days post-discharge significantly reduced the risk of 30-day mortality by 81% (95% CI 0.09–0.43). Conclusion: Patients admitted to hospital with AHF who experience a subsequent readmission within 20 days post-discharge are at increased risk of dying. However, early follow-up post-discharge may reduce this risk. Early post-discharge follow-up is vital to address this vulnerable period after a HF admission.